A Study on government size and tax structure - An, Jongseok (The Korea Institute of Public Finance SeoulKR, 2013)
Sheds light on the factors that trigger changes in tax and public burden ratios of Korea and other OECD member nations, along with international variations and will reveal relevant implications.